Cladoceran remains from the bottom sediments of the arctic lake arkto-pimberto in the pechora river delta - Frolova L.; Nigmatullin N.; Valieva E.; Nigamatzyanova G. (2020)
© 2020 International Multidisciplinary Scientific Geoconference. All rights reserved. Russian Arctic regions are most sensitive to global climate change. Their unique and fragile ecosystems are very dependent on freshwater. Beyond temperature rise, climate change is accompanied by shifts in precipitation and wind conditions, thereby causing floods, droughts, and altered mixing regimes, all having a serious impact on the abiotic and biotic structure. This work is relevant for better understanding of the biota of the Russian Arctic. Cladocerans are very promising for studying climate change risks owing to their inherently predictive nature. They form a rich functional group of zooplankton in ecosystem modeling and are distributed all over the world. However, the difficulty is that they are characterized by a very confusing taxonomy. In this paper, we considered the possible effects of large-scale climatic fluctuations on the dynamics of cladoceran community in the studied region. The aim of the study was to analyze of the subfossil cladoceran community of Lake Arkto-Pimberto in the Pechora River delta (in the northeast of European Russia). A total of 16 taxa were registered in the subfossil cladoceran community of the lake. Most of the identified taxa belong to the Chydoridae family. The representatives of the Bosminidae family were less frequent. Bosmina longispina was the dominant species. The subdominants were represented by Chydorus cf. sphaericus. Lake Arkto-Pimberto is inhabited mostly by northern and littoral species. The Shannon-Wiener diversity index varied between 0.86 and 1.85. According to the Pantle-Buck saprobity index, the lake is mesosaprobic. Significant changes in the composition of cladoceran communities were observed over time, thereby reflecting the environmental and climate changes in the region.